Today while surfing internet I found a Mathematical Prove of 4 = 5. Here is the solution I found for it.

let

– 20 = – 20

which can be written as

=> 16-36 = 25-45

by adding (81/4) on both sides we get

=> 16-36+(81/4) = 25-45+(81/4)

by writing the above eqn like this

=> ((4)2 -(2*4*(9/2)) +(9/2)2) = ((5)2 -(2*5*(9/2)) +(9/2)2)

which is of the form

=> (a-b)2 = a2 + b2 -2ab

here

=> a = 4 a = 5

b = 9/2 b = 9/2

from this we can write the above equation as

=> (4-(9/2)) 2 = (5-(9/2))2

by taking square root on both sides we get

=> +- (4-(9/2)) = +- (5-(9/2))

according to axioms when both sides are equal and having the same signs on both sides then both sides are positively equated to each other

=> 4 – (9/2) = 5 – (9/2)

by shifting -(9/2) from left side to right side we get

=> 4 = 5 – (9/2) +(9/2)

then as 9/2 gets cancelled we get

=> 4 = 5

To my knowledge of math this formula is incorrect. Wonder why?

Well the formula derivation reads, -20 = -20 implies 16-36 = 25-45, per mathematics rules, we need to solve problem not “reverse engineer” it. So -20 = -20 never implies 16-36 = 25-45. This “trick” is used quite a lot in application. Logically the derviation seems correct, but not mathematically. But in all it is nice trick. Good work whomsoever have found that.